PENINGKATAN LITERASI TEKNOLOGI MELALUI SOSIALISASI DAN PELATIHAN PEMROGRAMAN ARDUINO DI SMPN 6 MATARAM - Budiman, Djul Fikry; Alhabsyi, Defi; Wiryajati, I Ketut (Jurusan Teknik Elektro Universitas Mataram, 2024)
ABSTRACT The rapid development of technology in the Industrial Revolution 4.0 era requires the younger generation to have strong technological literacy to face future challenges. The Arduino programming training and socialization program at SMPN 6 Mataram is designed to enhance students' understanding of basic programming and electronics concepts through a practical approach. This training involves students in developing mini-projects using Arduino, such as simple robots and automation systems. The program consists of five stages: preparation, introduction, theory training, practice, and evaluation and follow-up. The evaluation results show that the three participant groups achieved relatively equal results, with the highest score in Group 1 (34%) and 33% for Groups 2 and 3. Minor differences between groups indicate the need for additional approaches to equalize understanding. This program is expected to serve as a model for technological literacy learning that can be implemented in other schools, enabling students to acquire relevant technological skills for the future